(untitled) (Advancements in Homeopathic Research, 2024)
Background: Hypertension is a prevalent medical condition with significant health implications. This retrospective case record analysis aimed to investigate the efficacy of Boerhaavia diffusa mother tincture in managing hypertension. The study utilized data from diverse healthcare settings affiliated with Sivaraj Homoeopathic Medical College and Research Institute, Salem. Methods: A total of 30 cases meeting the inclusion criteria, comprising both sexes aged between 30 to 75 years, diagnosed with hypertension based on clinical parameters (systolic BP >140 mmHg, diastolic BP >90 mmHg), and presenting common symptoms, were included. Exclusion criteria encompassed cases of secondary hypertension and those with incomplete follow-ups. The efficacy of Boerhaavia diffusa mother tincture was assessed by changes in blood pressure recorded during the treatment period. The study adhered to ethical guidelines, and all patients received Boerhaavia diffusa mother tincture as part of their therapeutic regimen. Results and Discussion: Among the 30 cases analyzed, 6 patients exhibited marked improvement, 10 demonstrated moderate improvement, and 10 showed mild improvement, while 4 cases showed no improvement. Notably, the majority of patients experienced marked symptomatic relief. Despite the positive trend observed in the outcomes, the study has limitations, including a small sample size and the absence of a control group. The lack of detailed information on dosage and treatment duration further restricts the generalizability of the findings. The retrospective nature of the analysis introduces potential biases, and confounding factors such as lifestyle changes were not systematically addressed. Conclusion: This retrospective case record analysis suggests a potential beneficial effect of Boerhaavia diffusa mother tincture in managing hypertension. The majority of patients experienced symptomatic relief, although caution is warranted due to study limitations. Future research, including well-designed randomized controlled trials with larger sample sizes, is needed to establish the efficacy and safety of Boerhaavia diffusa mother tincture in hypertensive patients.